Should serum biomarker monitoring replace primary antifungal chemoprophylaxis in patients with acute leukaemia receiving systemic anti-cancer therapy? A PRO/CON debate. Issue 4 (22nd July 2022) - Harrison, Thomas; Partridge, David
Abstract: Fungal infection exacts a severe burden on patients with acute leukaemia. Azole prophylaxis attempts to mitigate this impact but is associated with toxicity and cost as well as the potential to select for resistance. The development of biomarkers including galactomannan and β-1, 3-d -glucan may improve detection of early disease and thus reduce the need for prophylaxis, though these assays also have their limitations. In this debate, Howard et al . argue in favour of continuing chemoprophylaxis in patients with acute leukaemia receiving systemic chemotherapy, citing the multiple randomized control trials and meta-analyses that demonstrate its efficacy. Taynton et al. argue that fungal biomarker surveillance in the absence of primary antifungal chemoprophylaxis is a safe alternative that could reduce antifungal use and the development of resistance.